เศรษฐกิจ สังคม และการกระจายรายได้ในเขตเทศบาลนครแหลมฉบัง: Socio-Economic and Income Distribution in Laemchabang City Municipality - เต็งสุวรรณ์, ปาริฉัตร; ปั้นพงษ์, กอบกาญจน์ (Journal of Applied Economics and Management Strategy, 2018)
การศึกษานี้มีวัตถุประสงค์เพื่อศึกษาสภาพทั่วไป โครงสร้างพื้นฐาน ประชากร แหล่งที่มาของรายได้ ระดับรายได้ พฤติกรรมการใช้จ่าย การบริโภค ทรัพย์สิน ภาวะหนี้สิน และการออมของครัวเรือนในเขตเทศบาลนครแหลมฉบัง รวมถึงสภาพความเป็นอยู่ ตลอดจนการได้รับสวัสดิการความช่วยเหลือ และการใช้บริการจากภาครัฐของประชากรในชุมชน และนำข้อมูลที่ได้มาวิเคราะห์ถึงการกระจายรายได้ของครัวเรือนในชุมชน ตลอดจนวิเคราะห์สภาพปัญหาความต้องการและแนวทางในการพัฒนาชุมชน โดยใช้การเก็บรวบรวมข้อมูลปฐมภูมิจากแบบสอบถาม และการสัมภาษณ์ครัวเรือนตัวอย่าง ในปี พ.ศ. 2557 มาทำการวิเคราะห์ข้อมูลเบื้องต้นของครัวเรือน และทำการวิเคราะห์การกระจายรายได้ของครัวเรือนโดยใช้วิธีการวัดความไม่เท่าเทียมทางรายได้ หรือการหาค่าสัมประสิทธิ์จีนี และเส้นโค้งลอเรนซ์ ผลการศึกษาพบว่าครัวเรือนตัวอย่าง400 ครัวเรือนในเขตเทศบาลนครแหลมฉบัง ส่วนใหญ่มีการศึกษาระดับประถมศึกษาถึงปริญญาตรี ประกอบอาชีพหลักเป็นพนักงานบริษัทเอกชน รายได้เฉลี่ยต่อครัวเรือน 45,531.70 บาทต่อเดือน อาชีพรองคือค้าขาย รายได้เฉลี่ยต่อครัวเรือน 15,956.41 บาทต่อเดือน รายจ่ายส่วนใหญ่ของครัวเรือนใช้เพื่อบริโภคอาหารและเครื่องดื่ม รองลงมาเป็นรายจ่ายด้านหนี้สินโดยใช้เพื่อประกอบอาชีพ และเพื่อการศึกษา ในรูปแบบการใช้บัตรเครดิตมากที่สุด ทั้งนี้ครัวเรือนมีความต้องการให้หน่วยงานภาครัฐมีบทบาทในการพัฒนาสภาพแวดล้อมของชุมชน สำหรับผลการวิเคราะห์การกระจายรายได้พบว่าค่าสัมประสิทธิ์จีนี มีค่าเท่ากับ 0.3954 คือ การกระจายรายได้ของครัวเรือนมีการกระจายรายได้ที่เท่าเทียมกันอยู่ในเกณฑ์ที่ดี เนื่องจากมีค่าใกล้ 0 มากกว่า 1 หรืออยู่ในเกณฑ์ที่ไม่สูงเกินไปนัก และดีกว่าการกระจายรายได้ในภาพรวมของประเทศเล็กน้อย ส่วนความเหลื่อมล้ำทางด้านรายได้พบว่า กลุ่มคนรวยในเขตเทศบาลฯ มีรายได้รวมกันร้อยละ 30.86 ของรายได้ชุมชน ส่วนคนจน มีรายได้รวมกันร้อยละ 2.20 ของรายได้ทั้งชุมชน โดยคิดเป็นค่าความเหลื่อมล้ำทางด้านรายได้ต่างกัน 14.03 เท่า This research aimed to study the conditions of Laemchabang municipalities in terms of the infrastructure, demographic, source of revenue, level of income, spending habits, consumption, property, debt and household savings. Living conditions welfare assistance and the use of public services in the municipalities were also included in this study. The data were then analyzed to examine the distribution of household income and identify related problems in order to formulate development plan for the community. The study used primary data collected by questionnaire and interviews of sample households in 2014. Then, using the descriptive analyzes in the preliminary data and analyzed the distribution of household income by measuring inequality of income (the Gini Coefficient and the Lorenz Curve). The study found that most members of 400 household samples in Laemchabang municipalities had primary education to bachelor degree, had their own resident, worked in private companies as the main occupations (the average income was 45,531.70 baht per month), worked as merchants for the secondary occupations (the average income was 15,956.41 baht per month). The majority of household expenditures were used on food and beverages, followed by debt payment for occupation and study purposes, which were mostly paid through the credit cards. However, households wanted the government to take increasing role in improving the environment of the community. The analysis of income distribution shows that the Gini coefficient is equal to 0.3954. It means that the distribution of household income is remained well-balanced because the value is closer to 0 than 1 or it’s not too high. Furthermore, the value shows better in income distribution compared to the whole country. The income disparity between the richest and poorest group in the municipality reveals that the rich are earning combined 30.86 percent of the total income and the poor have 2.20 percent of total income, accounting for the disparity in income between the two groups equals to 14.03 times.